Revealing the Role of ASN Digital Literacy in Improving Budget Management Effectiveness: A Study of the Government of East Nusa Tenggara Province - Munawar, Munawar; Naiola, Fransiscus Nicodemus; Rantelobo, Alftred T. (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze the influence of Regional Government Information System (SIPD RI) synchronization, e-Budgeting, and resistance to change on the effectiveness of budget management in the Provincial Government of East Nusa Tenggara. A quantitative approach was employed using a survey method by distributing questionnaires to officials within the Regional Financial Agency of East Nusa Tenggara Province. Data were analyzed using multiple linear regression with the SPSS program. The results of this study indicate that the SIPD RI Synchronization variable has a positive and significant effect on the effectiveness of budget management, meaning that the more optimal the system synchronization, the higher the effectiveness of budget utilization. The E-Budgeting variable also shows a positive and significant effect on budget management effectiveness, demonstrating that the use of electronic-based systems supports transparency, efficiency, and accountability in regional financial management. The Change Resistance variable has a positive and significant effect on budget management effectiveness, which means that the better the management of resistance to change, the higher the effectiveness of budget management. Simultaneously, the three independent variables have a significant effect on the effectiveness of regional budget management. These findings emphasize that the success of regional financial management reform relies heavily on the synergy between digital systems and officials’ readiness to embrace change. Therefore, the Provincial Government of East Nusa Tenggara must strengthen training, technological infrastructure, and change management to achieve optimal budget management effectiveness.